If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying wx + b = yforx Reorder the terms: b + wx = yforx Solving b + wx = forxy Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1wx' to each side of the equation. b + wx + -1wx = forxy + -1wx Combine like terms: wx + -1wx = 0 b + 0 = forxy + -1wx b = forxy + -1wx Simplifying b = forxy + -1wx
| 6c-8=4c | | x+2=-6+72 | | 8x-2=x+4 | | v^2=37 | | 4-9=-13 | | f(x)=0.6+2.75 | | 2a-1=18 | | 4=m/7+5 | | 5n=-3n | | v^3=37 | | 4(x-4)+8=12 | | 2(x+4)+3=15 | | 55=x-48 | | 3x-2=8x-1 | | 6.43-10d=2.5 | | -2c+5=-c+2 | | 9x+15=14x-11 | | 2a-17+20a-9= | | -2(2k-4)=4(k-2) | | 8-5(2-x)=5+3(x-4) | | 5x-1+7x=90 | | -2747=41k | | 15X+1=6X+5 | | 10x-1=8x+1 | | 12(2k+11)=12(k+12) | | P-(-18)=16 | | 10y+4-7y=17 | | -3y=2y | | r+10=9 | | 18h+6(-8h-17)=-20h+18+20 | | 3pq-2rs=5 | | -3=a/4+1 |